2010
DOI: 10.1111/j.1745-6592.2009.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Arsenic Remediation from Groundwater in a Private Home

Abstract: Private wells are the source of drinking water for approximately 15% of households in the United States, but these wells are not regulated or monitored by government agencies. The well waters can contain arsenic, a known carcinogen that occurs in groundwater throughout the nation at concentrations that can exceed the Maximum Contaminant Level defined by the U.S. Environmental Protection Agency (10 ppb). In order to reduce arsenic exposure, homeowners can either rely on bottled water for drinking or install in‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…To lessen the risk of exposure to arsenic in drinking water, recommended preventative measures include point-of-use removal, modification of well depth, and/or use of an alternate water source (Alaerts and Khouri 2004; Pratson et al 2010). These solutions are rarely cost-effective, however, and may not be feasible in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…To lessen the risk of exposure to arsenic in drinking water, recommended preventative measures include point-of-use removal, modification of well depth, and/or use of an alternate water source (Alaerts and Khouri 2004; Pratson et al 2010). These solutions are rarely cost-effective, however, and may not be feasible in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretations of studies on the metabolic effects of arsenic are made difficult by the use of different doses and duration of exposure. Although the current MCL of arsenic stands at 10 ppb, higher levels of arsenic exposure continue to be an issue . We utilized a concentration that exceeds the MCL, and duration of exposure, though sufficient to be considered chronic, was relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses revealed that Melendiz Stream was carrying more arsenic to the lake. The conventional technologies that have been used to treat Ascontaminated water are coagulation (Karcher et al, 1999;Mamtaz and Bache, 2000;Baskan and Pala, 2009), adsorption to activated alumina (Bhattacharya et al, 2002;Spelman, 2003), ion exchange with strong-base anion-exchange resins (Spelman, 2003), and reverse osmosis (Bhattacharya et al, 2002;Pratson et al, 2010). The use of new adsorbents (Loukidou et al, 2003;Thirunavukkarasu et al, 2003;Pokhrel and Viraraghavan, 2006;Czerniczyniec et al, 2007;Sun et al, 2007;Su and Puls, 2008), in situ passive reactive barriers (Lindberg et al, 1997), bioremediation with chemical precipitation, and aquifer oxygenation are some of the emerging technologies for the in situ removal of As from groundwater.…”
Section: Processmentioning
confidence: 98%